Structural Racism, Immigration, and Social Hope: From the Brazilian Context to the State of Rio de Janeiro. (REMUNOM, 2026)
This article investigates the connections between structural racism, migration policies, and social hope in Brazil, focusing on the state of Rio de Janeiro. It adopts a qualitative, exploratory-analytical approach, guided by a critical and decolonial perspective, configuring itself as bibliographic and documentary research, with thematic content analysis and a case study. The theoretical framework draws on contributions from Brazilian social thought, decolonial critique, anti-discrimination law, and emancipatory pedagogies. The analysis reveals that structural racism is a historically constituted and re-actualized system, and that the Brazilian State has acted to perpetuate racial inequalities through the Land Law (1850), subsidized immigration policies for Europeans, and law as a technology of racialization. Structural barriers to Black immigrants persist, revealing ethno-racial selectivity. In Rio de Janeiro, necropolitics operates as a differential management of Black lives, while collectives such as Mães de Acari and Mães de Manguinhos emerge as resistance. Social hope, a collective political force, materializes in affirmative action, decolonial pedagogies, and engagement with future generations. It is concluded that confronting structural racism requires a profound transformation of social, economic, and symbolic structures, articulating social hope, political organization, and pressure from social movements.